2020
DOI: 10.2196/16225
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning–Based Prediction of Refractive Error Using Photorefraction Images Captured by a Smartphone: Model Development and Validation Study

Abstract: Background Accurately predicting refractive error in children is crucial for detecting amblyopia, which can lead to permanent visual impairment, but is potentially curable if detected early. Various tools have been adopted to more easily screen a large number of patients for amblyopia risk. Objective For efficient screening, easy access to screening tools and an accurate prediction algorithm are the most important factors. In this study, we developed an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Recently, AI diagnosis systems have been explored with CNNs using smartphone images such as skin cancer, 11 refractive error, 23 as well as middle ear diseases. Moshtaghi et al 24 have reported 100% sensitivity in abnormal TM detection using smartphone‐enabled otoscopes and developed a model to achieve the overall accuracy of 98.7% for the TM side and 91% for the perforation.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, AI diagnosis systems have been explored with CNNs using smartphone images such as skin cancer, 11 refractive error, 23 as well as middle ear diseases. Moshtaghi et al 24 have reported 100% sensitivity in abnormal TM detection using smartphone‐enabled otoscopes and developed a model to achieve the overall accuracy of 98.7% for the TM side and 91% for the perforation.…”
Section: Discussionmentioning
confidence: 99%
“…Deep learning, known as a subset of artificial intelligence, allows computational systems to learn representations directly from a large number of images without designing explicit hand-crafted features (LeCun et al, 2015). The applications of deep-learning techniques trained on color fundus images have produced systems with competitive or close-to-expert performance for an automatic detection of ophthalmic diseases, including diabetic retinopathy (Cao et al, 2020;Gargeya and Leng, 2017;Ting et al, 2017), age-related macular degeneration (Burlina et al, 2017;Grassmann et al, 2018;González-Gonzalo et al, 2020), retinopathy of prematurity (Wang et al, 2018;Mao et al, 2020), glaucoma (Hemelings et al, 2020), and other disorders (Shah et al, 2020); assessment of ocular and systemic risk factors such as age, gender, body mass index, and blood pressure; estimation of the refractive error (Poplin et al, 2018;Varadarajan et al, 2018;Chun et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This procedure takes time and, consequently, slows down the diagnosis process. To reduce the time needed for this process, machine learning has been recently used to predict refractive prescription from physical eye data obtained by wavefront aberrometers, 19 , 20 photorefraction images, 21 retinal fundus images, 22 other ophthalmologic devices, 23 and intraocular lenses characteristics. 24 The aim of this work is to develop a machine learning regression model that predicts patients’ subjective refractive prescription from the anterior corneal surface and ocular biometry.…”
Section: Introductionmentioning
confidence: 99%